Optimalisasi Peran Wanita Tani melalui Pemanfaatan Hasil Pekarangan dan Pemasaran Daring - Fatchiya, Anna; Puspita, Dyah Retna; Sita, Rai; Destriapani, Elsa; Putra, Rizki Aditya; Hastuti, Bekti Dwi (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Women's Farming Group (KWT) "Langgeng" in Godog Village, Polokarto, Sukoharjo Regency, remains predominantly involved in on-farm activities such as planting vegetables in home gardens, and has not yet maximized their off-farm potential. Although they recognize the potential of processing garden produce, they lack the knowledge to create marketable products and reach a wider market. The proposed solution is training to enhance their skills in processing and marketing agricultural products. The approach used is a problem-solving approach that includes problem identification, resource mobilization, program planning, community mobilization, and evaluation. The activities include (1) fostering an entrepreneurial spirit, (2) training in processing garden produce by making spinach sticks, (3) product packaging training, and (4) online marketing training. The results show an increased interest in entrepreneurship, improved skills in processing agricultural products, and the ability to use online platforms for marketing. This training optimizes the role of women farmers by supporting their skills in agricultural product management and online marketing.